Answer: THE LAST OPTION
Step-by-step explanation:
1. You have the following equation given in the problem:
![\frac{2}{3}x-\frac{1}{2}y=6](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3%7Dx-%5Cfrac%7B1%7D%7B2%7Dy%3D6)
2. If you multiply both sides of the equation shown above by 6, you obtain the following:
![\frac{2*6}{3}x-\frac{1*6}{2}y=6*6](https://tex.z-dn.net/?f=%5Cfrac%7B2%2A6%7D%7B3%7Dx-%5Cfrac%7B1%2A6%7D%7B2%7Dy%3D6%2A6)
![\frac{12}{3}x-\frac{6}{2}y=36](https://tex.z-dn.net/?f=%5Cfrac%7B12%7D%7B3%7Dx-%5Cfrac%7B6%7D%7B2%7Dy%3D36)
3. When you simplify the equation, you obtain the following equivalent equation:
![4x-3y=36](https://tex.z-dn.net/?f=4x-3y%3D36)
Answer:
Subtraction property of equality.
The first is C. r = 4(4/9)
the second one is B. h = 130
the second one is A. k = 7
i’m so sorry, they’re all wrong
Answer:
The equal amount is 525
.
Step-by-step explanation:
Given that,
Eric and his two sister shared amount of money in ratio2:7 respectively.
Amount with Eric = 300
It means,
2x = 300
x = 150
So,
7x = 7(150)
= 1050
As the remaining amount shared equally among the sister. So, the equal amount is 525
.